PECULIARITIES AND CHARACTERISTICS OF INDICATORS OF THYROID CANCER AMONG RESIDENTS OF TOMSK AND TOMSK REGION - I. N. Vorozhtsova; V. N. Latypova; T. V. Saprina; I. S. Beryozkina; A. P. Zima; A. I. Isaeva; S. V. Lunyova; L. A. Kudyakov; L. V. Pikalova (Бюллетень сибирской медицины)
The analysis of thyroid cancer incidence and its structure among different populations of Tomsk region is presented. We studied the report documents, the database of the Tomsk regional oncologic dispensary for the period 2008 to 2012. The clinical characteristics of patients with thyroid cancer were summarizes according to sex, age and place of residence. The papillary cancer was the most often diagnosed. It was found that in young patients, thyroid cancer was diagnosed more often in the stage 1 and 2. On the other hand, in elderly patients (above 60 years), thyroid cancer diagnosed at stage 3 and 4. In the Tomsk region, as elsewhere in the world, thyroid cancer is detected more often in women.